545 INCIDENCE OF INVOLVEMENT OF PARATRACHEAL LYMPHNODES IN SIEWERT AEG-I TUMORS. (17th September 2021) - Zacherl, Johannes; Radlspöck, Wolfgang; Albinni, Said; Höfle, Cordula; Kertesz, Viktoria; Öhler, Leopold; Schima, Wolfgang; Sitzwohl, Christian; Braun, Otto
Abstract: : Transthoracic esophagectomy with 2-field-lymphadenectomy (LAD) is the state of the art treatment of resectable adenocarcinoma of the distal esophagus (Siewert-Stein AEG type I) and may be performed in AEG II cardia cancers. However, it remains unclear whether paratracheal LAD contributes to a survival benefit. In this study we collected data regarding lymph node involvement of paratracheal nodes. Methods: From 2014 to 2019 consecutive patients were included in the prospective analysis. Patients underwent hybrid or open Ivor Lewis esophagectomy and 2-field LAD. Paratracheal tissue was removed from the right side of the trachea along the superior vena cava above the azygos vein up to the the upper thoracic aperture. Paratracheal lymph nodes were histologically evaluated separately from the nodes of other stations. Results: Ninety-five consecutive patients (12 were female, mean age 67, sd 10, AEG I 84, AEG II 11) were included in the prospective observation study. Seventy-two and 5 patients preoperatively received chemotherapy or radiochemotherapy, respectively. All of them underwent transthoracic esophagectomy (Ivor Lewis 93, McKeown 2—because of coexisting ultralong segment Barrett esophagus). Overall the mean (sd) lymph node count was 37 (12). In the right paratracheal region we found a median of 6 lymph nodes (range;1–22). In 42 (44%) patients positive lymph nodes were recorded, but there was no case with right paratracheal node involvement. Conclusion: In the present study paratracheal lymph node involvement was evaluated after transthoracic esophagecotmy with 2-field lymphadenectomy. Remarkably, despite a high proportion of overall lymphatic involvement we did not observe any paratracheal nodal metastasis. Larger studies may show whether paratracheal lyphmadenectomy is necessary during radical esophagectomy for AEG I and AEG II cancers.